A new method proposed to explore the feline's paw bones of contributing most to landing pattern recognition when landed under different constraints - Xu, Datao; Zhou, Huiyu; Zhang, Qiaolin; Baker, Julien S.; Ugbolue, Ukadike C.; Radak, Zsolt; Ma, Xin; Gusztav, Fekete; Wang, Meizi; Gu, Yaodong (Frontiers in Veterinary Science, 2022)
Felines are generally acknowledged to have natural athletic ability, especially in jumping and landing. The adage ‘felines have nine lives’ seems applicable when we consider its ability to land safely from heights. Traditional post-processing of finite element analysis (FEA) is usually based on stress distribution trend and maximum stress values. Therefore, this study investigated the cat forelimb biomechanical characteristics when landing from different heights using FEA and feature engineering techniques for post-processing of FEA. The results suggested that the stress distribution feature of the second, fourth metacarpal, the second, third proximal phalanx are the features that contribute most to landing pattern recognition when cats landed under different constraints. With increments in landing altitude, the variations in landing pattern differences may be a response of the cat’s forelimb by adjusting the musculoskeletal structure to reduce the risk of injury with a more optimal landing strategy. The combination of feature engineering techniques can effectively reveal intrinsic properties and identify the features that contribute most to pattern recognition under different constraints.